Hypovitaminosis D in healthy children in Central Thailand: prevalence and risk factors - Kanit Reesukumal (2017)
Background: There are limited data regarding the prevalence and risk factors relating to hypovitaminosis D in children of Thailand, a tropical country with abundant sunlight. The objective of this study was to assess the prevalence of hypovitaminosis D and examine factors associated with hypovitaminosis D in school-aged children in Bangkok, Thailand – a centrally located capital city. Methods: This cross-sectional study evaluated 159 healthy children (33.3% boys and 66.7% girls), aged 6 to 12 years, in Bangkok, Thailand (located at 13.45°N). Fasting plasma samples were examined for total 25-hydroxyvitamin D [25(OH)D] using electrochemiluminescence immunoassay. Demographic characteristics (age, sex, household income), past medical history (birth weight, allergic diseases, hospitalization), amount of sun exposure, anthropometric data, and selected biochemical tests were used to investigate for factors associated with hypovitaminosis D. Results: Overall, the mean ± SD level of plasma 25(OH)D was 64.0 ± 15.1 nmol/L. Hypovitaminosis D (< 75 nmol/L) was presented in 79.2% of subjects. Of these, the prevalence of vitamin D insufficiency and vitamin D deficiency were 59.7% and 19.5%, respectively. In univariate analysis, children with hypovitaminosis D (< 75 nmol/L) had a higher mean body mass index (BMI) percentile than the vitamin D-sufficient group (56.7 ± 33.9 vs. 42.6 ± 36.0; P-value = 0.04). Plasma PTH levels in the children with hypovitaminosis D were significantly higher than in the children with normal levels of vitamin D (4.34 ± 1.38 vs 3.78 ± 1.25 pmol/L; P-value = 0.04). In multivariate analysis, high BMI percentile and high PTH concentration were the parameters associated with 25(OH)D level < 75 nmol/L. Conclusion: The prevalence of hypovitaminosis D in healthy Thai children is very high, despite their exposure to sunlight, and that prevalence increases in children with a high BMI percentile. As a result, a formal recommendation for vitamin D supplementation in Thai children should be considered.